PENGARUH CITRA PERUSAHAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan Banaran 9 Resto Coffee and Tea Mugas Semarang) - Suri Sustikawati, 15.05.51.0191; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
This study aims to determine the effect of company’s image and service quality on satisfaction and its impact on customer loyalty. This study done on customers of Banaran 9 Resto Coffee and Tea Mugas Semarang. Research using a quantitative approach. The population in this study were customer of Banaran 9 Reto Coffee and Tea Mugas Semarang. The sampling technique used in this study was purposive sampling obtained a sample of 105 respondents. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis of this research is path analysis with the help of multiple linear regression. The results of the study show that the company’s image has a positive and significant effesct on customer satisfaction. Service quality has a positive and significant effect on customer satisfaction. The company’s image has a positive and significant effect on customer loyalty. Service quality has a positive and significant effect on customer loyalty. Satisfaction has no significant positive effect on customer loyalty. The direct effect of company’s image on customer loyalty is more effective than using satisfaction as a mediating variable. The direct effect of service quality on customer loyalty is more effective than using satisfaction as a mediating variable.